CHALLENGES AND OPPORTUNITIES IN INTERGRATING TPACK IN THE CLASSROOM - Mokhtar, Nor Zainiyah Norita (2021)
The session revolved around the challenges and opportunities that the language teachers will face when integrating TPACK in the classroom.